2022
DOI: 10.1002/fsn3.3061
|View full text |Cite
|
Sign up to set email alerts
|

Feruloyl oligosaccharides, isolated from bacterial fermented wheat bran, exhibit antioxidant effects in IPEC‐J2 cells and zebrafish model

Abstract: Feruloyl oligosaccharides (FOs) were produced by solid‐state fermentation of wheat bran using Bacillus subtilis, Bacillus licheniformis, and Saccharomyces cerevisiae, and its antioxidant activity was investigated using IPEC‐J2 cells and zebrafish embryo model. Preliminary structure analysis revealed that FOs has an average molecular weight of 11.81 kDa and consists of mannose, ribose, rhamnose, glucuronic acid, galacturonic acid, glucose, galactose, xylose, arabinose, and fucose. The obtained FOs possess super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Chen et al . (2022) found that FOs showed superior antioxidant activity in a zebrafish embryonic model. Under the condition of low dose, this paper was consistent with previous research results and showed that WBE had a good antioxidant function in vivo , and had a synergistic antioxidant effect with β‐carotene.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Chen et al . (2022) found that FOs showed superior antioxidant activity in a zebrafish embryonic model. Under the condition of low dose, this paper was consistent with previous research results and showed that WBE had a good antioxidant function in vivo , and had a synergistic antioxidant effect with β‐carotene.…”
Section: Resultsmentioning
confidence: 99%
“…Study has shown that the strong radical scavenging activity of FOs in WBE is closely related to the FA and xylose components of their structure (Chen et al ., 2022). Zhang et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Xyl and Ara were the main monosaccharides of wheat bran FOs. In total, ten types of monosaccharides in purified wheat bran FOs through co-culture fermentation were identified by Chen et al, and Xyl and Ara were the main types of monosaccharide with molar ratios of 33.42% and 29.81%, respectively (Chen et al, 2023). Zhao et al explored the antioxidant properties of different polymerisation degrees of wheat bran FOs.…”
Section: Monosaccharides Composition Of Purified Wheat Bran Fosmentioning
confidence: 99%